Development of models and software solutions for the recruiting agency information system - Liutenko, Iryna Victorivna; Motalyhin, Y. Y. (Одеська національна академія харчових технологій, 2021)
The work is devoted to the issues of automation of recruitment agencies activity. The use of information systems by recruiters, employers and job seekers significantly reduces the time to "close" the vacancy.
Keywords: software; software solutions; recruiting agency information system; information technology; recruitment agency; employer